2005
DOI: 10.1073/pnas.0409659102
|View full text |Cite
|
Sign up to set email alerts
|

Leptosphaeria rhodopsin: Bacteriorhodopsin-like proton pump from a eukaryote

Abstract: Bacteriorhodopsin-like proteins provide archaea and eubacteria with a unique bioenergetic pathway comprising light-driven transmembrane proton translocation by a single retinal-binding protein.Recently, homologous proteins were found to perform photosensory functions in lower eukaryotes, but no active ion transport by eukaryotic rhodopsins was detected. By demonstrating lightdriven proton pumping in a fungal rhodopsin from Leptosphaeria maculans, we present a case of a retinal-based proton transporter from a e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
187
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(199 citation statements)
references
References 27 publications
12
187
0
Order By: Relevance
“…In addition, opsin-encoding sequences have been identified in the genomes of the fungi Neurospora crassa (8), Fusarium fujikuroi (26), and Leptosphaeria maculans (17), but more examples are appearing as new fungal genomes become available. Recently, it has been demonstrated that the Leptosphaeria opsin acts as a bacteriorhodopsin-like proton pump (43). It was also shown that the Neurospora opsin NOP-1, when heterologously expressed in the yeast Pichia pastoris, forms an active photoreceptor exhibiting similar characteristics to the archaeal sensory rhodopsin II (7,9).…”
mentioning
confidence: 88%
“…In addition, opsin-encoding sequences have been identified in the genomes of the fungi Neurospora crassa (8), Fusarium fujikuroi (26), and Leptosphaeria maculans (17), but more examples are appearing as new fungal genomes become available. Recently, it has been demonstrated that the Leptosphaeria opsin acts as a bacteriorhodopsin-like proton pump (43). It was also shown that the Neurospora opsin NOP-1, when heterologously expressed in the yeast Pichia pastoris, forms an active photoreceptor exhibiting similar characteristics to the archaeal sensory rhodopsin II (7,9).…”
mentioning
confidence: 88%
“…fivefold) in WKI. Bacteriorhodopsins are lightdependent proton pumps in archaea and eubacteria, and related proteins occur in some eukaryotes (Waschuk et al, 2005;Wada et al, 2011). Their presence in marine eukaryotic phytoplankton genomes is thought to result from lateral gene transfer from bacteria (Slamovits et al, 2011).…”
Section: Variation In Diatom Metabolic Pathways Across Communitiesmentioning
confidence: 99%
“…A striking characteristic of these rhodopsins is their wide range of seemingly dissimilar functions. Some are light-driven transporters, such as the proton pumps bacteriorhodopsin (BR) 2 in haloarchaea, xanthorhodopsin in halophilic bacteria, proteorhodopsin in marine bacteria, Leptosphaeria rhodopsin in fungi, and halorhodopsin (HR) in haloarchaea and in bacteria (3,(13)(14)(15)(16)(17). These proteins generate an electrochemical membrane potential upon light activation, which is utilized by ATP synthase to produce ATP (18).…”
mentioning
confidence: 99%